Trends in the Development of the Efficiency of Management of Higher Education Institutions in Uzbekistan - Odinayeva N. F. (Research Parks Publishing LLC, 2023)
In recent years, large-scale reforms have been implemented in our country to increase the level of coverage of the population with higher education services, and to improve the quality indicators of the educational services provided to the population. In particular, President Mirziyoyev has set the task of